PENDIDIKAN KELUARGA MUSLIM DALAM MENANAMKAN TOLERANSI DI TENGAH MASYARAKAT MULTI AGAMA (STUDI KASUS DI DESA KAYUKEBEK KECAMATAN TUTUR): STUDI KASUS DI DESA KAYUKEBEK KECAMATAN TUTUR - Isnaini Maha Putri; Ahmad Marzuki; Ali Mohtarom (Education for Islamic Studies Department, Islamic University of Majapahit (Universitas Islam Majapahit) Mojokerto, Indonesia, 2023)
Indonesia has diverse cultures, ethnicities, races, languages and religions. Therefore, living in a pluralistic society requires the role of parents in instilling religious education and tolerance so that there is no conflict between religious communities. Good education patterns from parents will shape children's behaviour and morals as well. The purpose of this research is twofold; 1) To know the pattern of Muslim family education in instilling tolerance in Kayukebek Village, Tutur Sub-district. 2) To know the tolerance attitude of Muslim community in Kayukebek Village, Tutur Sub-district. The approach used by the researcher in this study is a qualitative approach with the type of field research using a case study design. The result of this research shows that 1) Educational patterns applied by Muslim families in instilling tolerance in children (a) exemplary education patterns, (b) habituation, (c) supervision, (d) advice and motivation, (e) enrolling children in Islamic educational institutions. 2) The attitude of tolerance of Muslim communities in Kayukebek Village (a) maintaining security at the entrance gate of Kayukebek Village on Nyepi night, (b) not doing activities that can interfere with tapa brata nyepi worship, (c) conducting social activities for distributing takjil at the Nongkojajar market by Tridatu (Hindu) and IPNU IPPNU (Islamic) youth organisations, (d) respecting Hindu communities by watching the ogoh-ogoh celebration